Analisis Wacana Kritis Program Blak-Blakan Edisi Keempat Jawa Pos Radar Semeru TV - Abdul Choliq; Muhammad Sidkin Ali (ARKANA: Jurnal Komunikasi dan Media, 2023)
The massive development of information technology causes print media to adapt quickly and precisely, one of which is through convergence. The Daily Newspaper Jawa Pos Radar Semeru has converged with social media to maintain its existence in the era of digital disruption. One of the social media shows that are widely appreciated by the public is the flagship program Blak-Blakan on the Radar Semeru TV youtube channel which airs every Wednesday night. In the fourth edition of the Blak-Blakan program with the topic "Batik and Lumajang's Typical Clothes, Whose?” going pretty warm. The Regent's Regulation Number 23 of 2016 concerning Official Clothing for Employees and Officials in the Lumajang Regency Government is considered to have caused polemics and controversies. The polemic of typical Lumajang clothing which describes this regional icon occurs because it has not been specifically regulated by the local government. This study uses the Critical Discourse analysis method from Teun A. van Dijk. The subject of the research is the Blasphemy program which will be broadcast on Wednesday, February 24, 2021. The object is the discourse that is developed through the Blak-Blakan program on Radar Semeru TV. The resource persons in the discussion agreed that the batik and Lumajang's typical clothes used by the State Civil Apparatus every 15th day must be reviewed so that the ideological and philosophical values ​​in them have meaning. Batik and Lumajang's typical clothes used by the State Civil Apparatus and the general public must be unique and reflect the Lumajang community. Batik and street vendors, which will later be agreed upon and ratified through local government regulations, are then registered as HAKI Lumajang so as not to be plagiarized by other parties.